The opinion of post graduate students on objective structured clinical examination in Anaesthesiology: A preliminary report - Jindal, Parul (Indian J Anaesth, 2016)
BACKGROUND AND AIMS: The scenario in medical education is changing with objective structured clinical examination (OSCE) being introduced as an assessment tool. Its successful implementation in anaesthesiology postgraduate evaluation process is still limited. We decided to to evaluate the effectiveness of OSCE and compare it to conventional examinations as formative assessment tools in anaesthesiology. METHODS: We conducted a cross-sectional comparative study in defined population of anaesthesiology postgraduate students to evaluate the effectiveness of OSCE as compared to conventional examination as formative assessment tool in anaesthesiology. Thirty-five students appeared for the conventional examination on the 1(st) day and viva voce on the 2(nd) day and OSCE on the last day. At the conclusion of the assessment, all the students were asked to respond to the perception evaluation questionnaire. We analysed the perception of OSCE among the students. RESULTS: Results showed a positive perception of the objective structured physical examination (OSCE) as well as structured 9 (25.7%), fair 19 (54.2%) and unbiased 13 (37.1%) with more standardised scoring 9 (25.7%). The students perceived OSCE to be less stressful than other examination. Thirty-one (88.5%) students agreed that OSCE is easier to pass than conventional method and 29 (82.5%) commented that the degree of emotional stress is less in OSCE than traditional methods. CONCLUSION: OSCE is better evaluation tool when compared to conventional examination.